OPTICAL ILLUSION IN IRAQI CONTEMPORARY PAINTING: رسل مظفر علي حسن (Al-Academy, 2016)
The excellence and uniqueness is what makes the artwork creative or not, and the School of Op. Art in Iraq came to reveal new phenomena distinct style, unique in units built, although a few worked in this aspect of the art, but they left their mark distinct, in the research, construction and installation of what binds them in heritage and civilization, it is a new vision of linking the past with the present, they adopt and engineering units may be architectural sometimes in composition, concluded a researcher at the end of the research to the main findings and conclusions, which is that more business was a square-shaped or semi-square, which is commensurate painting with visual, which is a set of vocabulary or repeat units, we do not find in all the work that is visual diagnostic business, so they was all abstractions and geometric curves